Synthesis of geranyl acetate by transesterification of geraniol with ethyl acetate over Candida antarctica lipase as catalyst in solvent‐free system. (18th June 2019) - Bhavsar, Kalpesh V.; Yadav, Ganapati D.
Abstract: Increasing environmental awareness has forced researchers to minimize the use of organic solvents in chemical synthesis. Modern biocatalysis is a way to  develop clean catalytic technologies. A process operating in solvent‐free condition using reusable biocatalyst, will be useful for the fragrance and flavour industry, which requires stringent specifications on impurities. A direct transesterification reaction of geraniol with ethyl acetate was carried out to produce geranyl acetate in a batch reactor using different immobilized enzymes. Among these, Novozyme 435 was the best catalyst for the synthesis of geranyl acetate in a solvent‐free medium. Parametric studies were conducted to optimize the conversion and yield. Overall, 83% conversion of geraniol with 100% selectivity to geranyl acetate was obtained at a mole ratio of 1:7 of geraniol to ethyl acetate, using 12.7 g L −1 Novozyme 435 at 60 °C for 2 h. At higher concentrations of acyl donor, it was noticed that the conversion of geranyl acetate was increased. The Lineweaver–Burk plots suggested a ternary complex with inhibition by ethyl acetate. The process is green, clean, and useful to the perfume and flavour industries. Abstract : Transesterification of geraniol with ethyl acetate was studied in a batch reactor to produce geranyl acetate to obtain 83% conversion of geraniol with 100% selectivity to geranyl acetate at a mole ratio of 1:7 of geraniol to ethyl acetate, using 12.7 g/L Novozyme 435 at 60 °C in 2 h. The Lineweaver‐Burk plots suggested a ternary complex with inhibition by ethyl acetate. The process is green, clean and useful to the perfume and flavour industry.